Visit‐to‐visit variability of blood pressure and risk of macrovascular and microvascular complications in patients with type 2 diabetes: A Chinese primary‐care cohort study. Issue 11 (28th November 2022) - Deng, Ying; Liu, Yin; Zhang, Shengchao; Yu, Hanbing; Zeng, Xiaozhou; An, Rongrong; Chen, Zhenyuan; Sun, Na; Yin, Xiaoxv; Dong, Yue
Abstract: Background: We evaluated the effects of visit‐to‐visit variability of systolic blood pressure (SBP) and diastolic blood pressure (DBP) on macrovascular and microvascular complications among patients with type 2 diabetes. Methods: A total of 11 043 patients with type 2 diabetes from primary healthcare institutions between January 2010 and June 2020 were included. The visit‐to‐visit blood pressure variability was calculated using three metrics: SD, coefficient of variation (CV), and average real variability (ARV), obtained over a 12‐month measurement period. The associations of visit‐to‐visit blood pressure variability with macrovascular and microvascular complications were evaluated using multivariate‐adjusted Cox proportional hazards models, and hazard ratio (HR) with 95% confidence interval (CI) were reported. Results: There were 330 macrovascular events and 542 microvascular events. Compared to those for participants with the lowest quartile of SD of SBP and DBP, increased risks were observed in patients with the highest quartile of SD of SBP and DBP for macrovascular complications (SD‐SBP: HR = 1.78, 95% CI: 1.24–2.57; SD‐DBP: HR = 2.20, 95% CI: 1.50–3.25) and microvascular complications (SD‐SBP: HR = 1.85, 95% CI: 1.39–2.46; SD‐DBP: HR = 1.82, 95% CI: 1.36–2.44). CV and ARV of SBP and DBP also had statistically significant associations with macrovascular and microvascular complications. The optimal variability of blood pressure target was SD of SBP <6.45 mm Hg and SD of DBP <4.81 mm Hg. Conclusions: Visit‐to‐visit blood pressure variability may be a potential predictor for macrovascular and microvascular complications in patients with type 2 diabetes. Abstract : Highlights Evidence on the associations between visit‐to‐visit variability of blood pressure and risks of macrovascular and microvascular complications in patients with type 2 diabetes was insufficient and controversial. This study showed that greater variability of blood pressure was related to increased risks of macrovascular and microvascular complications for patients with type 2 diabetes. Our findings identified the optimal variability of blood pressure target for patients. Clinical professionals should also remain vigilant about the visit‐to‐visit fluctuation of blood pressure. 摘要: 背景: 我们评估了在2型糖尿病患者就诊间收缩压(SBP)和舒张压(DBP)的变异性与大血管和微血管并发症的关系。 方法: 纳入2010年1月至2020年6月在基层医疗机构就诊的11043例2型糖尿病患者。就诊间的血压变异性使用在12个月的测量期内获得的三个指标计算:标准差(SD), 变异系数(CV)和平均实际变异性(ARV)。用多变量校正的COX比例风险模型评估就诊间的血压变异性与大血管和微血管并发症的关系，并报告95%可信区间(CI)的危险比(HR)。 结果: 大血管事件330例，微血管事件542例。与SBP和DBP标准差最低四分位数的受试者相比，SBP和DBP标准差最高四分位数的患者发生大血管并发症(SD‐SBP:HR=1.78，95%CI:1.24‐2.57, SD‐DBP:HR=2.20，95%CI:1.50‐3.25)和微血管并发症(SD‐SBP:HR=1.85，95%CI:1.39‐2.46, SD‐DBP:HR=1.82，95%CI:1.36‐2.44)的风险增加。SBP和DBP的CV和ARV也与大血管和微血管并发症有统计学意义的相关性。最佳血压指标变异性为:SBP标准差<6.45 mm Hg，DBP标准差<4.81 mm Hg。 结论: 就诊间的血压变异性可能是2型糖尿病患者大血管和微血管并发症的潜在预测指标。